1996
DOI: 10.1097/00019606-199609000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Variations in c-erbB-2 Proto-oncogene Status in Breast Cancer Tumors as Detected by Two Different cDNA Probes

Abstract: We examined 232 breast carcinomas for c-erbB-2 amplification by Southern analysis using two different cDNA probes. Using these same probes, 95 of these tumors were also examined for mRNA expression by Northern analysis. Amplification was detected in 20 and 17% of the tumors with the probes pHER 2 and pCER 204, respectively, but only 10% showed amplification with both probes. A significantly higher incidence (p < 0.01) of mRNA overexpression was detected with the pHER 2 probe (34%) compared with the pCER 204 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Analysis of the 79 canine mammary tumors revealed ErbB-2 expression in about 50% of the benign tumors, such as adenomas of the simple and complex types and 19.1% in the adenocarcinomas. The percentage of canine malignant tumors expressing ErbB-2 in this study was of the same order as that of human mammary cancers (20% to 30%), but lower than that of canine mammary tumors (74%) reported previously [14,17,[21][22][23][24]. Nakopoulou et al [22] demonstrated that ErbB-2 membrane staining of breast cancers was due generally to oncogene amplification, although gene amplification does not seem to be the only underlying genetic alteration responsible for ErbB-2 overexpression.…”
Section: Discussionsupporting
confidence: 56%
“…Analysis of the 79 canine mammary tumors revealed ErbB-2 expression in about 50% of the benign tumors, such as adenomas of the simple and complex types and 19.1% in the adenocarcinomas. The percentage of canine malignant tumors expressing ErbB-2 in this study was of the same order as that of human mammary cancers (20% to 30%), but lower than that of canine mammary tumors (74%) reported previously [14,17,[21][22][23][24]. Nakopoulou et al [22] demonstrated that ErbB-2 membrane staining of breast cancers was due generally to oncogene amplification, although gene amplification does not seem to be the only underlying genetic alteration responsible for ErbB-2 overexpression.…”
Section: Discussionsupporting
confidence: 56%
“…There is a growing clinical demand for HER2/ neu analysis of current and archived breast carcinoma specimens. There are a variety of methods available to determine the HER2/ neu status of cancer, and Southern hybridization 14 and fluorescent in situ hybridization 15–17 as assays for gene amplification, and northern hybridization, 14 in situ hybridization, 18 immunoassays 19 and immunohistochemistry 14,20–23 as assays for overexpression are widely known. Among them, the immunohistochemical assay is most convenient in both routine clinical practice and in clinical research studies because of: (i) no need to collect fresh sample; formalin‐fixed, paraffin‐embedded specimens are acceptable; (ii) short detection time; (iii) no requirement of apparatus to detect fluorescence; and (iv) ease of standardization by automatic staining.…”
Section: Discussionmentioning
confidence: 99%
“…First, if a gene is only partially amplified, the tumor cells cannot express the normal product of the cyes oncogene or may express an abnormal product. Second, other defects often occur in tumors, such as transcription errors or mutations in the regulation or promoter sequences, which could result in increased expression of the protein without amplification of the gene [17,20,24].…”
mentioning
confidence: 99%